2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chip LED Sensor Module for Fat Thickness Measurement using Tissue Phantoms

Abstract: We tested the feasibility of noninvasive fat thickness measurements by using a diffuse optical method with variable source-detector pairs. A light source module composed of 770 nm low-power chip LEDs and a photodetector were used in this study. The tissue phantoms are composed of a fat and a muscle layer made with gels with appropriate absorption/scattering coefficients. The fat thickness was varied from several to 30 mm. Based on this preliminary study, it is concluded that the noninvasive fat thickness measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The improvement offered by the cosine corrector in the NIR body fat measurement demonstrates the importance of appropriate equipment and device selection in NIR configurations. This was in agreement with a study by Hwang et al ., in which they used varied types of LEDs with different view angles (lamp at 20° over miniature chip at 120°) in NIR phantom experiments resulting in higher sensitivity by the miniature chip25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement offered by the cosine corrector in the NIR body fat measurement demonstrates the importance of appropriate equipment and device selection in NIR configurations. This was in agreement with a study by Hwang et al ., in which they used varied types of LEDs with different view angles (lamp at 20° over miniature chip at 120°) in NIR phantom experiments resulting in higher sensitivity by the miniature chip25.…”
Section: Discussionmentioning
confidence: 99%
“…Past NIR subcutaneous fat studies using simulations and phantom measurement methods have found that light reflection increases logarithmically with the thickness of the fat layer2529. The logarithmic relationship can be attributed to the high influence of fat on light scattering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the distance between the LED and photodetector increased, the detected light intensity rapidly decreased. However, the backward scattering light carried more fat information with more LEDs, which improved the resolution and signal to noise ratio [15]. Therefore, it could be inferred that P 1 and P 4 were the two major factors in the models and skin color P 5 did not influence the measurement distinctly.…”
Section: Regression Modelsmentioning
confidence: 98%
“…Measuring SAT thickness by near-infrared (NIR) light is another noninvasive and convenient approach. Previous work investigated the reflected intensity as a function of fat thickness, from which the fat thickness measurement could be derived with curve fitting procedure (Hwang et al 2006, Song et al 2009. Several studies using an optical device called a Lipometer (from Medical University Graz, Austria) indicated that there were close relationships between thickness of SAT layers and body fat measured by DXA (Jürimäe et al 2007) and BIA (Jürimäe 2005).…”
Section: Introductionmentioning
confidence: 99%